HUMAN RESOURCES DEVELOPMENT IN CHILDREN EYE HEALTH SERVICES IN SOUTH SULAWESI - Amalius, Ahmad Ashraf; Muhiddin, Habibah Setyawati; Ichsan, Andi Muhammad; Faisal, Andi Akhmad; Kamaruddin, Muhammad Irfan; Akib, Marlyanti N.; Kotha , Satya Prabha (Majalah Oftalmologi Indonesia, 2023)
Introduction: Children eye health are one of the most common problems in ophthalmology that are getting attention globally and nationally especially in South Sulawesi. To optimize its services quality and quantity of human resources are required. This study aims to report the human resources development in children eye health services in South Sulawesi. Methods: Surveys were carried out in several districts to assess the availability of human resources in children eye health services. Creating collaborations with several institutes such as Faculty of Medicine, Hasanuddin University and related professional organizations. Conducting several trainings in provinces, districts, subdistricts, village, and urban village. Results: Preparation and dissemination of materials and media on prevention of blindness in children, improvement of human resources in the form of District Trainer training in 24 districts that recruited 98 people who were ready to become trainers. For 2 years conducting tiered training at 24 districts, they produced human resources of 1,395 officers at the Puskesmas, 11,145 posyandu cadres, and 3,826 teachers. The results of this built system revealed that 3,248 paediatric patients were screened with vision problems, 3,528 toddlers in Integrated Health Centre were screened and referred to Health Centre as many as 426 toddlers, and at the School Health Unit it was recorded that 173,778 children were screened and there were 28,845 (17%) children who had visual disturbances. Conclusion: Development of human resources in children eye health in Indonesia was not only the responsibility of the government and the health sector but also need cross-sectoral roles.